Investigation of the Mechanism of Precipitation of the Ti3Al in Two-Phase Titanium-Aluminium Alloy - Popov, A.A.; Lugovaya, K.I.; Zhilyakova, M.A.; Petrov, R.I.; Popova, E.N. (KnE Engineering, 2019)
Changes in the formation processes of the ordered Ti3Al phase (α2 phase) was studied depending on the heat treatment in the Ti – Al alloy. It was shown that hightemperature treatment in a single-phase α-region, followed by supercooling at different temperatures, leads to a more active release and growth of dispersed particles than after preliminary processing from the β-region. Keywords: titanium alloys, intermetallics, ordered phases